Politeia and the past in Xenophon and Isocrates - Atack, C (De Gruyter, 2018)
Both Xenophon and Isocrates use the past to analyse and comment on political problems of the present, and to provide authority for political programmes of the present and for the future, through connecting them to revered past figures and mythologies. For both, idealised versions of historical Greek communities provide a counterpoint to the disappointments and decline of present-day politics and politicians. Figures from the distant past become exemplars for political action in the present, and their achievements, and the political and social arrangements under which those achievements were completed, models for political reform. Xenophon and Isocrates draw on the wider Greek politeia tradition of writing about political and social customs, educational practices, and institutions, seen in both free-standing pamphlets, and sections embedded within longer historical, rhetorical and philosophical works.1 With the exception of Xenophon’s Lacedaimoniōn Politeia, both Xenophon and Isocrates embed politeia elements in larger works.